Greenhouse Gases: A Review of Losses and Benefits - Audi, Marc; Ali, Amjad; Kassem, Mohamad (International Journal of Energy Economics and Policy, 2019)
This study provides a review of benefit and losses of greenhouse gases. For the last decades, the average global temperature is rising on the surface as well as on the oceans. There are a number of factors behind this rise, but the main cause of this rise is anthropogenic increase in greenhouse gases (GHG). The anthropogenic factors comprise of burning of fossil fuel, coal mining, industrialization etc. During the last century, the CO2 concentration increased by 391 PPM, CH4 and N2O have reached at warming levels. The rise in overall temperature is changing the living pattern of humans and it also damages the economy as well as ecosystem for other living species. The rising GHG concentration may also have some positive effects on the economy, but it has heavy costs as well. GHGs are responsible for the change in climate which include a rise in sea level, ice melting from ice sheets and ocean acidification and climate change is responsible for the other damages like low fresh water resources, damage to the coastal system, damage to human health and raise the issue of food security. Keywords: Greenhouse gases, health, food, natural resources JEL Classifications: P28, P36, L66 DOI: https://doi.org/10.32479/ijeep.8416